1974
DOI: 10.1080/00220973.1974.10806305
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Analysis of Variance, the Welch Procedure and a Box Procedure to Heterogeneous Variances

Abstract: Numerous studies have documented the robustness of t and F to heterogeneous variances under the restricted condition of equal n's. Likewise, the distortion of 01. in the presence of unequal n's and variances has been demonstrated in both mathematical and empirical studies. Several investigations, however, have shown the Welch technique to be robust to this disturbing situation in the two group case. The present study was addressed to the k group AOV situation. Monte Carlo methods were employed to contrast seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 17 publications
1
61
0
3
Order By: Relevance
“…-Our simulations and those ofKohr and Games (1974), Tomarken and Serlin (1986), and Wilcox et al (1986), indicate that the standard ANOV A F may be severely affected by variance heterogeneity. Unweighted-means ANOV A is even more affected (Milligan et al 1987).…”
Section: Alternatives To the Anovamentioning
confidence: 96%
See 1 more Smart Citation
“…-Our simulations and those ofKohr and Games (1974), Tomarken and Serlin (1986), and Wilcox et al (1986), indicate that the standard ANOV A F may be severely affected by variance heterogeneity. Unweighted-means ANOV A is even more affected (Milligan et al 1987).…”
Section: Alternatives To the Anovamentioning
confidence: 96%
“…For extremely unequal sample sizes (max/min ratio = 4), W may be too liberal; in fact neither test is robust to some patterns of variance heterogeneity, especially for many treatments (m > 4). However both Kohr and Games (1974) and Tomarken and Serlin ( 1986) found that W is robust for three or four treatments when the max/min ratio of sample sizes was 3. Clearly, very unequal sample sizes should be avoided.…”
Section: Alternatives To the Anovamentioning
confidence: 99%
“…For the normal case this result was already noted by Tukey in Chapter 30 of [6]. The levels ak are called apparent significance levels by Tukey [9], k-mean significance levels by Duncan [2], and nominal levels by Einot and Gabriel [3].…”
Section: X;d·mentioning
confidence: 67%
“…No exact test of homogeneity is then available; however a test proposed by Welch [10] seems to provide a highly satisfactory approximate test. (See Kohr and Games [6] for a comparison with several other tests.) The values of a 2 , • • • , as defined in Sections 4, 5 and 6 are then no longer exact and in fact depend slightly on the true values of the variance ratios.…”
Section: Most Powerful Test When Sis Oddmentioning
confidence: 99%
“…Many authors have highlighted available procedures for analyzing data that violate either the assumption of normality or the assumption of variance homogeneity. Brown and Forsythe (1974), Kohr and Games (1974) others demonstrated the general effectiveness (i.e., Type I error control) of Welch's (1938Welch's ( , 1951 two-sample and omnibus test statistics with heterogeneous variances. In addition, Keselman, Cribbie and Zumbo (1997), Wilcox (1995;, Yuen and Dixon (1973), and Zimmerman and Zumbo (1993a), among many others, have demonstrated the effectiveness of several alternatives to traditional parametric tests that can be used with nonnormal data, including nonparametric test statistics and tests with robust estimators (e.g., trimmed means).…”
Section: Introductionmentioning
confidence: 99%